Comparison between Monitored Anesthesia Care Combine with Fentanyl under Ilioinguinal and Iliohypogastric Nerve Block and Spinal Anesthesia for Inguinal Herniorrhaphy in Saraburi Hospital - Suleesathira, Pollapat (Srinagarind Medical Journal, 2019)
Background and Objective: The purpose of this study was to compare the outcomes of spinal anesthesia and ilioinguinal-hypogastric nerve block (IHNB) combine with infusion of fentanyl with monitored anesthesia care (MAC) for inguinal herniorrhaphy in Saraburi hospital. Methods: A prospective, randomized controlled trial was conducted for elective inguinal herniorrhaphy. Forty patients were assigned equally into spinal anesthesia group (Group S) and IHNB with MAC group (Group M). In Group M, fentanyl was injected 2 mcg./kg. intravenously 5 minutes before IHNB was performed and then infused continuously until the operation was over. Two groups were compared to assess hemodynamic values, oxygen saturation, observer’s assessment of alertness/sedation scale (OAA/S), visual analogue scale (VAS) and patients' and surgeon's satisfaction. Ephedrine administration,urinary retention and postoperative nausea vomiting were observed. Results: The systolic, diastolic blood pressure and heart rate of Group S was significantly lower than Group M. Ephedrine was administered in Group S significantly higher than Group M. OAA/S, oxygen saturation and respiratory rate weren’t significantly different between the two groups. VAS in the recovery room were higher in Group M (p =0.001). VAS at the ward weren’t significantly different between the two groups. Patient’s satisfaction scores were higher in Group M (p=0.001) but surgeon's satisfaction scores were higher in Group S (p =0.005). The number of the patients who suffered from urinary retention, postoperative nausea vomiting weren’t significantly different between the two groups. Conclusion: IHNB under MAC combine with fentanyl is safe for elective inguinal herniorrhaphy. This approach can be applied for outpatient surgeries.